ANALISIS BEBAN KERJA DAN ARAH PENATAAN ORGANISASI PERANGKAT DAERAH (STUDI PADA TIGA SATUAN KERJA PERANGKAT DAERAH KABUPATEN MUSI RAWAS) - Zulpikar, Zulpikar (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
The work load by definition is a scope of work to do and to be a responsibility of the assigned position and or a unit of organization. If the scope of organization is determined as in the work responsibility, the effective, efficient, rational, and proportional organization will be realized. The object of the study is the work load including the subject of structural officer of echelon IV in Public Assistant of Local Secretariat, the Civil Registry Office, Board of Regional Development Planningof Musi Rawas Regency. Referring to the finding, the job/work description should be clearly and specifically stated based on their own authority and responsibility (Public Assistant of Local Secretariat, the Civil Registry Office, Board of Regional Development Planning), the system of work relation and work procedure through making Standard Operating Procedure (SOP) and the fulfillment of Employee?s needaccording to the work load referred to requirement of work competence.